An exploratory research about ethical issues on a smart toy: The Hello Barbie case study - Albuquerque, Otávio de Paula; Fantinato, Marcelo; Peres, Sarajane Marques; Hung, Patrick C. K. (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS), 2022)
Smart toys are becoming increasingly present in children's lives, reinforcing the relevance of this market niche. Advances in user interfaces and artificial intelligence have been incorporated into smart toys to provide greater autonomy and inductive reasoning skills through machine learning. However, machine learning embedded in smart toys not only brings benefits but also potential problems of bias, possibly related to prejudice and discrimination. This work aims to explore Mattel's Hello Barbie smart toy in a case study, seeking to analyze its knowledge base and conversational functionality to identify possible ethical issues that could cause harm to children. The intention is to show unknown risks that can occur in the evolution's process of smart toys.